Conjunctival incisions for trabeculectomy and their relationship to the type of bleb formation-A Preliminary Study (1987)
The bleb which develops following trubeculectomy may be diffuse or cystic in nature. Cystic blebs can he complicated by infection, leakage of aqueous, astigmatism and problems related to contact lens wear, whereas diffuse blebs are not associated with such problems. We report a preliminary prospective photographic evaluation of bleb formation following each of three types of conjunctival incision: (a) fornix bascd (b) straight limbus based and (c) curved limbus based. The vascular patterrn and morphology of the drainage bleb formed was dependent upon the type of conjunctival incision made. The fornix based flap was found most likely to give rise to a diffuse bleb with a normal vascular pattern.